Ayurvedic Approach in Management of Avabahuka (Adhesive Capsulitis) (AYUSHDHARA, 2023)
Avabahuka is a condition where the Vata near the base of the shoulder constricts the Siras, preventing the shoulder joint from moving. The signs of adhesive capsulitis, also referred to as frozen shoulder or Avabahuka, may co-occur. The clinical illness known as frozen shoulder causes painful restrictions to both passive and active shoulder movements. A 25-year-old male patient arrived at the OPD with the main complaints of left shoulder joint pain, stiffness, restricted movement, and loss of sleep brought on by pain in the previous 12 months. The clinical presentation of the symptoms significantly improved when the patient underwent Panchakarma therapy, which includes Jambira-Pinda Sweda, Nrap Vallabha Taila Nasya, and the use of specific Ayurvedic medications.